Comparison of Erythropoietin alone with Erythropoietin plus oral Ascorbic Acid in the Treatment of Anemia in Chronic Kidney Disease Patients - Mansoor Abbas Qaiser, Zain ul Aibideen, Mubashar Yameen, Zarmina Roop, Muhammad Awais Saleh, Fateh Sher Chattah (Journal of Rawalpindi Medical College, 2021)
Objective Of the Study: To compare efficacy of “Oral ascorbic acid in combination with Erythropoietin” with “standard dose of erythropoietin alone” in renal anemia in terms of mean hemoglobin rise. Introduction: Recombinant human erythropoietin (rhEPO) has a vital role in management of anemia in CKD (chronic kidney disease) patients. In the last decade, Ascorbic acid (AA) has emerged as a potential therapy to improve anemia probably by enhancing iron mobilization. We have conducted this study to compare the mean hemoglobin rise after treatment with standard dose erythropoietin alone with standard dose erythropoietin plus Oral ascorbic acid in CKD patients who were suffering from anemia. Materials & Methods: A total of 70 patients of CKD with anemia, 18 to 70 years of age of both genders were included. Patients with laboratory proven iron deficiency anemia, obvious blood loss, pernicious anemia, hyperparathyroidism and contraindications for erythropoietin or ascorbic acid treatment were excluded. The patients which were selected randomly placed in two groups. Group A (erythropoietin alone) & Group B (erythropoietin plus oral ascorbic acid), by using lottery method. Outcome variable like hemoglobin was measured at 2, 4 and 6 months. Results: Mean age was 48.90 ± 13.53 years. Male to female ratio was 1.6:1 with 43 (61.43%) males and 27 (38.57%) females. Mean pre-therapy hemoglobin was 9.40 ± 1.03 g/dl in the Group A while it was 9.42 ± 0.98 g/dl (p-value = 0.901) in Group B and mean post-therapy hemoglobin in the Group A was 9.34 ± 1.06 g/dl while in the Group B was 10.37 ± 1.16 g/dl with p value of 0.0002 which is statistically significant. Conclusion: The study concluded that standard dose erythropoietin plus Oral ascorbic acid in CKD anemia is more effective as compared to erythropoietin alone. Keywords: Chronic kidney disease, Erythropoietin, Ascorbic acid, Anemia.